Perception and Prevention Efforts Toward HIV Transmission AmongFemale Sex Workers and Seafarers - Aditya Aditya; Annisa Nurrachmawati; Nur Rohmah (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Female sex workers (FSWs) and seafarers are high-risk groups for HIV transmission, especially in isolated coastal regions such as Muara Berau, East Kalimantan. Complex interactions between economic dependency, limited health service access, and gender inequality contribute to inconsistent condom use and high-risk sexual behavior. Although global studies have examined these dynamics, Indonesian maritime and port contexts remain understudied Objective : To summarize, analyze, and interpret research findings related to perceptions and preventive behaviors against HIV transmission among FSWs and seafarers, emphasizing condom negotiation, structural barriers, and contextual risk factors in coastal communities Research Methods/ Implementation Methods : A narrative review was conducted using 32 scientific articles published from 2010 to 2025, retrieved from national and international journals. The literature was analyzed thematically using theoretical frameworks including the Health Belief Model (HBM), Social Ecological Model (SEM), and Theory of Gender and Power to identify determinants of condom use, behavioral change, and prevention barriers Results : Findings reveal that HIV prevention among FSWs and seafarers is influenced by economic pressures, client dominance, social stigma, and limited access to health services. Knowledge and perceived benefits of condom use are often high, but behavioral consistency remains low. Structural barriers—mobility, gender power imbalance, and lack of outreach—exacerbate risk exposure. Conclusion/Lesson Learned : Effective HIV prevention in coastal Indonesia requires multilevel interventions addressing socio-economic, behavioral, and structural determinants. Empowering FSWs’ negotiation capacity, enhancing seafarers’ awareness, and strengthening outreach-based health programs are essential to close the knowledge–practice gap